Alcohol consumption and depressive symptoms over time: a longitudinal study of patients with and without HIV infection. - Sullivan, Lynn E; Goulet, Joseph L; Justice, Amy C; Fiellin, David A (Drug and alcohol dependence, 2011)
The impact of alcohol consumption on depressive symptoms over time among patients who do not meet criteria for alcohol abuse or dependence is not known.
Keywords: Adult; Aged; Aged, 80 and over; Alcohol Drinking; Alcoholism; Cohort Studies; Data Collection; Depression; Female; HIV Infections; Hospitals, Veterans; Humans; Longitudinal Studies; Male; Middle Aged; Prospective Studies; Psychiatric Status Rating Scales; Substance-Related Disorders; United States; Young Adult